EVALUASI KURIKULUM SEKOLAH DASAR DALAM MENILAI EFEKTIFITAS DAN RELEVANSI PEMBELAJARAN DI SDN SIRNARAJA - Fitri Fauziah Nur; Sofi Mutiara Insani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research evaluated the effectiveness and relevance of the curriculum at SDN Sirnaraja using a mixed methods approach, involving students, teachers, parents and principals. Data was collected through classroom observation, questionnaires, interviews and document analysis. The results show that learning is quite effective, with students feeling engaged and teaching methods that support understanding of the material. However, the use of technology in learning is still lacking. The curriculum is rated relevant by most students and parents, but needs to be improved to cover the latest developments in technology and 21st century skills. Research recommendations include improving technology infrastructure, teacher training and collaboration with the community. The implementation of these recommendations is expected to improve the quality of education and prepare students for future challenges. In addition, continuous monitoring and regular evaluations are proposed to ensure the sustainability and adaptation of the curriculum according to the evolving needs of the times. Support from the government and other stakeholders is also needed to realize the proposed changes and create a more conducive and innovative learning environment.